1966
DOI: 10.1104/pp.41.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Changes During Recovery from Sodium Deficiency in Atriplex

Abstract: Siunmary. Althoughi the concenitrationi of sodium in leaves of Atriplcxl plants increased rapidly after receiving sodiumi, no growth response was detectable for about 6 days. It was found that respiration rate increased to its maxillum n vithin 3 days. Chlorophyll content also increased from an early stage, whereas the concentrations of sugars and starch did niot inierease, and ratios of soluble to total nitrogen did not (lecrease until later.The respiratory response appears to be specific to sodiumii as diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The paradigm that C 4 species benefit particularly substantially, and indeed in many, albeit not all, cases require Na + as an essential nutrient, is now widely accepted (Harmer and Benne 1945;Barbier and Chambannes 1951;Brownell and Wood 1957;Brownell 1965;Alekseev and Abdurakhamanov 1966;Brownell and Jackman 1966;Brownell and Crossland 1972;Marschner 1995;Pessarakli and Marcum 2000;Pessarakli 2001;Subbarao et al 2003). Important exceptions include the leading C 4 crops corn and sorghum, which have been shown not to benefit from Na + addition (Ohta et al 1988;Ohnishi et al 1990;Subbarao et al 2003).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
See 1 more Smart Citation
“…The paradigm that C 4 species benefit particularly substantially, and indeed in many, albeit not all, cases require Na + as an essential nutrient, is now widely accepted (Harmer and Benne 1945;Barbier and Chambannes 1951;Brownell and Wood 1957;Brownell 1965;Alekseev and Abdurakhamanov 1966;Brownell and Jackman 1966;Brownell and Crossland 1972;Marschner 1995;Pessarakli and Marcum 2000;Pessarakli 2001;Subbarao et al 2003). Important exceptions include the leading C 4 crops corn and sorghum, which have been shown not to benefit from Na + addition (Ohta et al 1988;Ohnishi et al 1990;Subbarao et al 2003).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…From beet to chocolate: the classic literature-Na + benefits are common It has long been known that Na + can be of benefit to the growth of algae and cyanobacteria (Allen and Arnon 1955;Simonis and Urbach 1963;Brownell and Nicholas 1968), but, for higher plants, the reputation of the ion as a toxic one has held sway (Maathuis 2007;Munns and Tester 2008;Kronzucker and Britto 2011;Cheeseman 2013), and the vast majority of higher-plant literature on the ion has focused on this aspect, even though studies in a wide variety of species, including such important cultivated ones as tomato, potato, carrot, cacao, and cereals, have demonstrated the potential benefit of the ion for higher-plant growth as well (Wheeler and Adams 1905;Lehr 1941;Lehr and Wybenga 1955;Woolley 1957;Williams 1960;Brownell 1965;Brownell and Jackman 1966;Montasir et al 1966;El-Sheikh et al 1967;Hylton et al 1967;Draycott and Durrant 1976;Galeev 1990;Takahashi and Maejima 1998;Gattward et al 2012). It is important to emphasize that every substance has a threshold below which it is not toxic, in accordance with the "sola dosis facit venemum" (only the dose makes the poison) principle, famously attributed to Theophrastus Bombastus von Hohenheim (Paracelsus), but, for Na + , beneficial effects are seen well into the range of concentrations that would be considered high for ordinary nutrient ions, such as NO 3 − , NH 4 + , or K + , and, in the cases of halophytes, go far beyond that (Flowers and Colmer 2008).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…The basal culture solution had the following composition expressed in ftmoles/liter: KNO3, 5,000: Ca(NOj). 4,000; Lemm. in 1954 (1), when it was demonstrated that small amounts of the element are specifically required for growth.…”
mentioning
confidence: 99%
“…DISCUSSION Sodium chloride has often been shown to increase the growth of halophytes such as Atriplex spp. (Ashby and Beadle 1957;Brownell and Jackman 1966;BlumenthalGoldschmidt and Poljakoff-Mayber 1968;Greenway 1968;Jennings 1968). The data presented above show that the beneficial effect of NaCI on growth of A. halimu8 is mainly in the alleviation of the adverse effect of moisture stress conditions, such as are brought about by low atmospheric humidity (Figs.…”
Section: Figures 1 and 2 And The Data Inmentioning
confidence: 88%